The Role of regional integration in promoting economic Growth and development: A Regional and Comparative Analysis of the European Union and MERCOSUR - Hajar, Dewi (Professorline, 2024)
This article examines the Role of regional integration in promoting economic Growth and development using a regional and comparative analysis between the European Union (EU) and MERCOSUR (Mercado Común and del Sur). The author shows that regional integration can offer more extensive markets, freer trade, closer cooperation, and more excellent stability. However, the author also acknowledges the challenges and obstacles that the two regional blocs face, such as differences in economic, political, and social structures, imbalance of power, conflict of interest, and lack of coordination and consensus. The author suggests that the EU and MERCOSUR can learn from each other's experiences and increase dialogue and cooperation to solve their problems and achieve common goals.